Abnormal emotion processing, but intact fairness and intentionality considerations during social decision-making in schizophrenia - de la Asuncion, Javier; Docx, Lise; Sabbe, Bernard; Morrens, Manuel; de Bruijn, Ellen R. A. (Frontiers in Psychology, 2015)
Schizophrenia is a severe mental disorder that is highly characterized by social cognitive impairments. Most studies investigating these impairments focus on one specific social domain such as emotion recognition. However, in daily life, processing complex social situations relies on the combination of several social cognitive and affective processes simultaneously rather than one process alone. A modified version of the economically based Ultimatum Game was used to measure the interplay between fairness, intentionality, and emotion considerations during social decision-making. In this task, participants accept or reject fair and unfair monetary offers proposed intentionally or unintentionally by either angry, happy, neutral, or sad proposers. Behavioral data was collected from a group of schizophrenia patients (N = 35) and a group of healthy individuals (N = 30). Like healthy participants, schizophrenia patients differentiated between fair and unfair offers by rejecting unfair offers more compared to fair offers. However, overall patients did reject more fair offers, indicating that their construct of fairness operates within different margins. In both groups, intentional unfair offers were rejected more compared to unintentional ones, indicating a normal integration of intentionality considerations in schizophrenia. Importantly, healthy subjects also differentiated between proposers’ emotion when rejecting unfair offers (more rejections from proposers depicting angry faces compared to proposers depicting, happy, neutral, or sad faces). Schizophrenia patients’ decision behavior on the other hand, was not affected by the proposers’ emotions. The current study thus shows that schizophrenia patients have specific problems with processing and integrating emotional information. Importantly, the finding that patients display normal fairness and intentionality considerations emphasizes preservation of central social cognitive processes in schizophrenia.